2021
DOI: 10.1108/ijmf-03-2021-0155
|View full text |Cite
|
Sign up to set email alerts
|

Debt structure: a solution to the puzzle of capital structure

Abstract: PurposeThe purpose of this paper is to investigate the relation between debt structure and future external financing and investment. Furthermore, it aims to analyze the association between debt structure and future financial performance.Design/methodology/approachVolume, maturity, possessing collateral and having priority at the settlement date are the dimensions of debt structure that have been employed in this paper. The sample consists of 1,060 firm-year observations from Tehran Stock Exchange corporations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 91 publications
(180 reference statements)
0
1
0
Order By: Relevance
“…Another stream of research investigates the impacts of CSR reporting on information asymmetry from the output perspective. In other words, researchers believe that if CSR reporting can mitigate the information asymmetry between the parties, then lower levels of information asymmetry can result in the reduction in external financing costs and better access to financial resources because lower levels of information asymmetry are associated with the reduction in external financing costs (Poursoleyman, Mansourfar, & Abidin, 2020 , 2022 ). Employing an international setting consisting of 3594 firms from 31 stock indices, García‐Sánchez et al ( 2019 ) found that CSR reporting is negatively associated with financial constraints.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Another stream of research investigates the impacts of CSR reporting on information asymmetry from the output perspective. In other words, researchers believe that if CSR reporting can mitigate the information asymmetry between the parties, then lower levels of information asymmetry can result in the reduction in external financing costs and better access to financial resources because lower levels of information asymmetry are associated with the reduction in external financing costs (Poursoleyman, Mansourfar, & Abidin, 2020 , 2022 ). Employing an international setting consisting of 3594 firms from 31 stock indices, García‐Sánchez et al ( 2019 ) found that CSR reporting is negatively associated with financial constraints.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Despite extensive research on the relationship between debt financing and financial performance, empirical studies have so far yielded conflicting findings (Poursoleyman, Mansourfar, & Abidin, 2023). According to a 2018 study by Deng, there is a link between debt financing and financial performance that is negative but statistically insignificant.…”
Section: Statement Of the Problemmentioning
confidence: 99%